Epidemiological profile of women victims of sexual violence in the city of Blumenau-SC (Revista Brasileira Multidisciplinar, 2026)
This paper deals with sexual violence against women, rape being the most common act in Brazil. Statistics show that many cases are still underreported, the result of a culture of violence and gender inequality. Sexual violence has serious consequences, such as injuries, post-traumatic stress disorder, depression and other health problems. The main objective is to analyze the epidemiological profile of women victims of sexual violence in the municipality of Blumenau-SC, from 2017 to 2022, in addition to knowing the current scenario of cases, identifying the profile of victims, considering the characteristics and factors associated with violence and identifying the profile of aggressors, considering the proximity of the aggressor to the victims. The work was carried out by collecting data from the SINAN website (DataSUS), public data, with the variables used being age, race, education and relationship with the aggressor and, in relation to violence, the year of reporting, type and whether it was repeated or not. In view of this, it is essential to identify the profile of victims in order to provide adequate care by health professionals, as well as for the community to be able to promote campaigns and actions aimed at raising awareness and preventing cases of sexual violence.
Keywords: Violence against women; Sexual violence; Epidemiologic profile; Awareness raising